Micromorphological and anatomical studies on petals of 11 Turkish Onosma L. (Boraginaceae) taxa (Bangladesh Journal of Plant Taxonomy, 2009)
The petal epidermis and petal anatomy of 11 taxa of Onosma L. were studied using light and scanning electron microscopy. Differences in epidermal patterns were observed on the dorsal surface. Domed epidermal cells and non-papillae epidermal cells were seen on the petal surface. Papillae types were lithops, cone-like, finger-like or skittle-cell type. Areolate and rugose types were observed on the non-papillae surface. Principal anatomical structures of petals were similar. Micromorphological features on dorsal surfaces of petals could be useful for species-level diagnosis along with other selected morphological and micromorphological features.